Competency Development of Disaster Prevention and Mitigation Officers at the Office of Disaster Prevention and Mitigation, Bangkok Metropolitan Administration - ยศมา, อำนาจ (CRRU Law, Political Science and Social Science Journal, 2021)
In this thesis, the researcher examines the competencies of the disaster prevention and mitigation officers; investigates the factors affecting the competency development of the officers under study; and studies guidelines for the competency development of the officers under investigation. In this mixed-methods research investigation using both quantitative and qualitative research approaches, the sample population consisted of 200 subjects. The research instruments consisted of a questionnaire for the officers under study and a form for interviewing eight executives of the Office of Disaster Prevention and Mitigation, Bangkok Metropolitan Administration (BMA). Findings are as follows: The core competencies of the officers under study were found to be at a high level in the following descending order: teamwork; morality and ethics; professional expertise accumulation; good service; and achievement orientation. The line of work competencies were at a high level in the following descending order: the decision to solve crisis situations; seeing risks; having emotional maturity; awareness and strictness; safety; encouraging the participation of all sectors; having disciplines; and rescuers’ spirits. The factors affecting the competency development of the officers under study were at a high level in the following descending order: job characteristics; security and advancement; salary and welfare; superiors’ policies; and organizational management. The guidelines for the competency development of the officers under study commenced from the recruitment by providing opportunities for the persons having qualifications appropriate for the job positions. The development focused on the development of competencies in accordance with work performance i.e. workshop training, as well as basic-advanced programs for firefighters and rescuers. The evaluation was conducted using the fairness system, monitoring and follow-up of work performance with the methods of observation, an evaluation form, and interviews with the evaluation committee of the Office of Disaster Prevention and Mitigation. Recommendations The core competencies of the officers under study should be developed in all aspects or should be encouraged to develop in an increasing manner i.e. the aspects of achievement orientation; teamwork; and morality and ethics. The line of work competencies of the officers under investigation should be developed in all aspects or should be encouraged to develop in an increasing manner i.e. the decision making to solve crisis situations; seeing risks; strictness; safety; and emotional maturity. The guidelines for competency development should be in consonance with the determination of qualifications for recruitment; the selection appropriate for work positions; and an evaluation system for work performance with a focus on the morality system. This is to ensure fairness in the Office of Disaster Prevention and Mitigation in the future.